Role of linguistic and sociocultural diversity in reading literacy achievement: a multilevel approach. (21st August 2014) - Netten, Andrea; Luyten, Hans; Droop, Mienke; Verhoeven, Ludo
Abstract : This study examined how linguistic and sociocultural diversity have an impact on the reading literacy outcomes of a representative sample of 3, 549 first‐language (L1) and 208 second‐language (L2) fourth‐grade students in the Netherlands. A multilevel modelling analysis was conducted using Progress in International Reading Literacy Study 2006 data to explore to what extent linguistic background, socioeconomic status (SES), home and school literacy environment and reading attitudes explain differences in reading literacy achievement. Significant differences between L1 and L2 students were found with regard to reading literacy achievement, SES and the home and school literacy environment. Multilevel modelling analysis showed 34.7% of explained variance in reading literacy achievement, whereby the student level accounts for most of the explained variance. In the final model, linguistic background, SES, home and school literacy environment and reading attitudes were found to have a significant effect on reading literacy achievement.